Boston City Hospital on Harrison Avenue, 1861 - Hawes, Josiah Johnson (Tufts Archival Research Center, 2005)
Street-level view northeast of Pavilion One, located on the northeast grounds of the Boston City Hospital on Harrison Avenue, opposite of Worcester Square. Pavilion One housed the original surgical ward 7 in diamter (image is round), 8 x 8 overall Photographs